The Effectiveness of Utilizing Non-Green Public Space in Untia Fishermen Settlement - Andi Edy Satar; Idawarni Asmal; Edward Syarif (EPI International Journal of Engineering, 2021)
Public Space in a settlement will be effective and useful if it has three intrinsic values, namely democratic, meaningful and responsive. Then the existence of people and how they play a role in space is important in reviewing the public nature of a space. The effectiveness of a public space can be assessed from the level of utilization by the community on the types of activities and social interactions of the people in it. Currently, the use of Non-Green Public Space is still not in line with expectations, namely the realization of a comfortable, productive and sustainable space, marked by the lack of community social activities in the Untia Fisherman Settlement Non-Green Public Space (NGPS). The purpose of this study was to evaluate the effectiveness of the use of Non-Green Public Space in the Untia Fisherman Settlement in the form of Taman Bermain Delta and Plaza Park. The research method used in this study uses descriptive qualitative research methods because it describes the research location at the time of observation and compares standards and or theories with the facts of the availability of Non-Green Public Space (NGPS) in the settlements using the Good Public Space Index (GPSI) analysis tool. From the results of the analysis, it was found that the availability of the Taman Bermain Delta Non-Green Public Space in the Untia Fisherman Settlement was related in terms of utilization, as well as in terms of accessibility to the Non-Green Public Space, elements (Comfortable, Relaxation, Passive and Active engagement Discovery), as well as the availability of supporting facilities and infrastructure were still lacking. both in terms of quality and quantity. Re-effectiveness of the function and nature of the existence of the Non-Green Public Space in the Untia Fisherman Settlement requires cooperation from various parties.